Long-term optimization of regional power sector development: Potential for cooperation in the Eastern Nile region? - Mondal, Md. Hossain Alam; Ringler, Claudia (Elsevier, 2020)
This paper develops a regional TIMES modelling framework for the electricity sector of the Eastern Nile Basin region, including Egypt, Ethiopia and Sudan, to assess the potential of energy trading for cross-border collaboration in this rapidly growing sector. Four alternative scenarios are developed for the 2014–2050 period to assess national and regional benefits of alternative energy development strategies. The study finds that electricity trading scenarios out-perform a reference scenario that assumes no energy trading, lowering systems cost by 4.5–7.2%. Total systems costs are lower, even when transmission costs for trade are considered. Costs are also lower with increased generation from renewables compared to investments without regional trade. Investing in renewables has important co-benefits, such as improved energy security and reduced greenhouse gas emissions. Supporting energy trade not only reduces systems costs, but can also strengthen cooperation in the region, as reflected in the energy trading efforts of the East African Power Pool and the transboundary collaboration efforts of the Nile Basin Initiative.